ANALISIS PENGEMBANGAN PARIWISATA PENDUKUNG KAWASAN ARJUNO AGROTECHNOPARK KABUPATEN PASURUAN - Dzulkifli, Muhammad; Ahmad Zaki Fadlur Rohman; Damayanti , Ratnaningsih; Samsudin, Asep (Pusat Penelitian Dan Pengabdian Masyarakat STIEPARI Semarang, 2023)
The Bromo-Tengger-Semeru Destination is a tourist destination managed by the Government through the Bromo-Tengger-Semeru National Park Office (TN-BTS), so to increase regional income and economic growth for the people of Pasuruan Regency, the Pasuruan Regency Government must develop TN-BTS supporting destinations in the sub-districts around the TN-BTS. One of the potential tourist attractions supporting the Bromo Tengger Semeru Area is the Arjuno Agrotechnopark Area which will be developed in Purwosari District and Purwodadi District. This analysis provides an overview of potential; problem; impact analysis from the socio-cultural, legal, environmental, and economic perspectives; area management plans with integrated routes, integrated tourism plans and tourism development strategies. The research in this activity is of an applied research nature, namely with the desire to answer or find solutions to solving problems related to policies so that the resulting solutions can be implemented as a basis for making policies for making the Master Plan for the Development of the Arjuno Agrotechnopark Tourism Area in Pasuruan Regency. Data collection was carried out by: a) desk study, b) field observations, c) documentation, and d) interviews. The results of the analysis state that there are two tourist routes that can be integrated into various tour packages according to the direction of entry of tourists from various cities in Java. The impacts that can arise from tourism activities in this area are in the form of social, cultural, economic and environmental impacts. Development is carried out with a 5-year medium-term strategy with four programs